Magnetic field simulation of golay coil - Ahmad, Rashdi Shah; Shaari, Amiruddin; Chew, Teong Han (Ibnu Sina Institute for Fundamental Science Studies, Universiti Teknologi Malaysia, 2008)
In the field of magnetic resonance imaging (MRI), besides the main magnetic field and the radio frequency (RF) system, the gradient coils system also plays an important role in signal acquisition. Generally, there are 2 transverse gradient coils and 1 longitudinal gradient coil. In this research, the magnetic field (or gradient) generated by the conventional transverse coil, namely the Golay coil was mapped. The calculation algorithm of the magnetic field generated was written in C-programming language, compiled by the GNU-compiler collection (GCC) and was based on a forward analytical approach by using the Biot-Savart Law. The data was then visualized by Gnuplot. The magnetic field was successfully calculated and plotted using open-source softwares running under Ubuntu operating system and will provide valuable data especially for gradient coil designer